The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011 41st IEEE International Symposium on Multiple-Valued Logic 2011
DOI: 10.1109/ismvl.2011.12
|View full text |Cite
|
Sign up to set email alerts
|

Using Multiple-Valued Logic Decision Diagrams to Model System Threat Probabilities

Abstract: Abstract-System security continues to be of increasing importance. To effectively address both natural and intentional threats to large systems, the threats must be cataloged and analyzed. Extremely large and complex systems can have an accordingly large number of threat scenarios. Simply listing the threats and devising countermeasures for each is ineffective and not efficient. We describe a threat cataloging methodology whereby a large number of threats can be efficiently cataloged and analyzed for common fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The identified parameters are then stored in the MDD data structure as edge value annotations. Using a piecewise polynomial approximation, we can analyze multi-state systems similarly to the previous MDD-based analysis methods [5] [8] [6] [7] that use a single value for each probability. Instead of a single value, we assign a polynomial to each edge of an MDD, as shown in Fig.…”
Section: Curve-fitting Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified parameters are then stored in the MDD data structure as edge value annotations. Using a piecewise polynomial approximation, we can analyze multi-state systems similarly to the previous MDD-based analysis methods [5] [8] [6] [7] that use a single value for each probability. Instead of a single value, we assign a polynomial to each edge of an MDD, as shown in Fig.…”
Section: Curve-fitting Methodsmentioning
confidence: 99%
“…This concept is used for disastertolerance analysis in [3] where a mark-up language, CyTML, represents cyber-threat trees and a companion parser converts the CyTML into a corresponding MDD with edge annotations. The cyber-threat tree approach is generalized for application to other analysis tasks in [5]. The work in [6] extends that of [5] by using an Edge-Valued MDD (EVMDD) software to provide additional experimental results and analysis of the computational memory resource requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For fast assessment of the state probabilities, many methods based on binary decision diagrams (BDDs) [2]- [4], [6], [23] and multi-valued decision diagrams (MDDs) [10], [13], [20]- [22] have been proposed, and they have attracted much attention in recent years. Especially, MDD based methods hold promise, as [17] showed that an MDD based method is more efficient than a BDD based one.…”
Section: Introductionmentioning
confidence: 99%
“…We have also applied multiple-valued logic decision diagrams to threat trees to determine large-scale system threat probabilities [10]. Our initial approach assumed that system components operated independently.…”
Section: Introductionmentioning
confidence: 99%